2011
DOI: 10.1007/s00502-011-0827-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of electromagnetic and mechanical phenomena in the end-winding region of three-phase induction machines*

Abstract: The 3-D geometry of the motor end-region consisting of the end-winding together with the motor cross-section, housing and complementary construction parts is very complex, which makes the analytical computations of the electromagnetic phenomena related to the end-region very cumbersome and non accurate. Furthermore, owing to the complicated geometry, also the preparation of the numerical model is extremely time consuming and numerical simulation very computationally pretentious. The aim of this paper is to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…1) have been calculated using a network simulation model based on the Park transformation. In contrast to (Stermecki et al, 2011), in this research the rotor current excitation has been neglected. The assumption has been made that the field components provoked by the short-circuit stator currents dominate over the rotor fields.…”
Section: Electromagnetic Simulationmentioning
confidence: 98%
See 1 more Smart Citation
“…1) have been calculated using a network simulation model based on the Park transformation. In contrast to (Stermecki et al, 2011), in this research the rotor current excitation has been neglected. The assumption has been made that the field components provoked by the short-circuit stator currents dominate over the rotor fields.…”
Section: Electromagnetic Simulationmentioning
confidence: 98%
“…As pointed out in the introduction, a transient time-stepping numerical simulation has been carried out. Similarly to the method presented in (Stermecki et al, 2011) where the magnetic field and forces have been evaluated for the synchronous generator nominal operation conditions, the non-conforming FE mesh approach has been employed in this research, too. Since the magnetic problem has been described using the T, F -F formulation, the stator current excitation (J) has been represented by a current vector potential T 0 satisfying the following condition:…”
Section: Electromagnetic Simulationmentioning
confidence: 99%
“…Whereas the previous two problems required two-dimensional models, the simulation of the end-windings of electrical machines and computing the corresponding inductances as well as losses in the structural parts has made the development of three-dimensional models necessary [6][7][8]. In Fig.…”
Section: Electromagnetic Analysismentioning
confidence: 99%
“…Under the action of the electromagnetic forces, mechanical responses such as deformation, stress, elastic strain, etc., will be caused. The deformation (displacement) and stress distribution of the stator end winding in single-phase short circuit, double-phase short circuit, and three-phase short-circuited case are studied [8,11,12]. Yang Zhao employed the finite element software ABAQUS/CAE to obtain the transient magnetic force and it is found that the vibration mode of the end windings is ellipse [12].…”
Section: Introductionmentioning
confidence: 99%